The identity of Cirsium henryi (Asteraceae, Cardueae) - Jin, Zi-Chao; Chen, You-Sheng (Phytotaxa, 2021)
Cirsium forrestii, C. melanoplepis and C. taliense have been usually treated as synonyms of C. henryi. Our critical examination of type materials and field observation reveals that all the three taxa are actually not conspecific with C. henryi. Cirsium forrestii and C. taliense should be both reinstated as independent species, whileas C. melanoplepis is in fact conspecific with C. forrestii. Cirsium taliense is found conspecific with C. chlorolepis, and C. chlorolepis is newly treated as a synonym for C. taliense. We modified the description of C. henryi, which in fact only occurs in Hubei province of China. Lectotypification is proposed for C. henryi and C. taliense.